2019
DOI: 10.5194/adgeo-45-397-2019
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric maps from multi-temporal analysis of Sentinel-2 data: the case study of Limassol, Cyprus

Abstract: Abstract. During the last years, various methods and techniques have been used to estimate the seafloor topography with high accuracy. The topography is considered an important component for marine applications since several activities and infrastructures are being carried out at the bottom, column and surface of the sea. In this, study, freely and open distributed optical satellite images were used to obtain bathymetric data for shallow waters, (until 30 m below sea level) based on timeseries analysis of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
0
33
0
4
Order By: Relevance
“…The multi-scene compositing approach addressed limitations inherent in conventional methods and reduced the impact of turbidity, performing better than the standard "pick the best scene" method that relies on a single image (Figures 3 and 4c vs. Figure 4a in Cape Lookout; and Figure 10e vs. Figure 10a,c in Saint Joseph Bay). The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The multi-scene compositing approach addressed limitations inherent in conventional methods and reduced the impact of turbidity, performing better than the standard "pick the best scene" method that relies on a single image (Figures 3 and 4c vs. Figure 4a in Cape Lookout; and Figure 10e vs. Figure 10a,c in Saint Joseph Bay). The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19].…”
Section: Discussionmentioning
confidence: 64%
“…The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A summary of each paper is given in the following. Gomes and Almeida (2019) employed Apatite fissiontrack (AFT) analyses to Southern Brazil and Uruguay samples, aiming to understand the low temperature history of the Dom Feliciano Belt Segment. Twenty-four samples were dated, and confined track lengths of twenty samples were measured.…”
mentioning
confidence: 99%